Fungsi Tradisi Ta'Ziah di Iran Menurut Ulama Syiah - Imam Subchi (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2004)
Iranian is well known as Syiah school followers. One of their tradition whichis internalized strongly and heredited fromgeneration to generation is ta'ziah. This heredition is contributed by their Mollah. The people who visit and build the graveof their Mollah will gain syafa'at Raulullah.